The Current Unilateralist Counterattack on Unionism and Collective Bargaining - Barkin, Solomon (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1986)
The swing to political conservatism in the eighties encouraged anti-union groups to weaken and dismantle both the unionmovement and the labor parties. The author, in his analysis, illustrates the developments and contents of the new policies in the field of industrial relations noting that another equally dramatic account may be set forth in the fields of wage policy and social welfare programs.